Background in forest engineering to work in urban forestry - de Sousa, Kelly Iapuque Rodrigues; de Melo, Lucas Amaral; Reis, Michele Valquíria Dos (National Journal of City Management, 2022)
Urban Forestry provides multiple ecosystem services and contributes to the resilience of cities. However there are no studies that discuss the background of professionals who work in this field. Thus, it was proposed to analyze the presence of the subject of Urban Forestry in Forest Engineering courses in Brazil. Searches were carried out in the e-MEC Registry to locate the Universities, and on their websites to find the Pedagogical Project or the Curriculum Matrix. To analyze the contents of the Syllabus, the IRAMUTEQ software was used. 68 Forest Engineering courses were located, which are offered by 60 universities and cover 24 states of the country, highlighting the North and Southeast regions, which offer 20 and 16 courses, respectively. 59 Pedagogical Projects were found and there was a lack of standard in the structure and content of the document. In the Curriculum Matrices, 79 subjects on Urban Forestry were identified, but only 27 exclusively address the theme. It was noticed that most of the subjects offered are complementary; only 12 are mandatory and, at the same time, only on Urban Forestry. The subject "Urban Forestry and Landscaping" appears 25 times. However, the two themes have different approaches and, in this case, the main focus was on Landscaping. The analysis of Text Segments of the 65 Syllabuses showed that most of the texts were about Landscaping. It was concluded that there is a deficiency in the background in Forest Engineering in Brazil concerning Urban Forestry, due to the low number of compulsory subjects offered.